GOOD FAITH TO STANDARD CONTRACT IN THE BUSINESS LAW PERSPECTIVES - TRIANA, YENI (Human Sustainability Procedia, 2018)
The problem with the standard contract, that the debtor is a weak party, is often unable to conduct bargaining position, making it less favorable for the debtor, therefore the implementation of good faith in standard contact is preferred as a guarantee that benefits both parties in the standard contract. The formulation of the problem, how the influence of good faith to the standard contract in the perspective of business law.The purpose of this study is to analyze the influence of good faith towards standard contract in business law perspective. The usefulness of this research is useful for the parties to understand good faith in the standard contract in the business law perspective.The research method used is normative law, this research is done by literature study. The data analysis technique used is juridical analysis, the object which is the data of this research is the study of the law based on the judge's decision in its consideration to cancel a standard contract that is not based on good faith in business law perspective.The result of this research is that good faith in a standard contract is a barrier against a standard contract made unilaterally by the creditor, in the absence of a bargaining position on the debtor. So the judge can cancel the contract, based on the principle of good faith, which is based on a sense of propriety and justice in society to uphold the rule of law, especially business law. A good faith is accepted as a justification to cancel the contract as a consideration of one party's imbalances.The conclusion that the good faith to the standard contract is a disability-containing agreement of abuse of undue influence to the judge's judgment to cancel the agreement in the contract. Suggestion, that good faith is expected to be a positive law and regulated in contract law, thereby enriching the repertoire of business law.Keywords: Good faith, Standard contract, and business actor.